Caracterização de lixiviados de aterros sanitário e industrial da região metropolitana de Belo Horizonte - Marina Andrada Maria (2010)
Despite being planned engineering works, the landfills generate leachate that can cause impacts to the environment and damages to man. This work aims to characterize the physical-chemical and biological the leachate of four sanitary landfills and one industrial landfil of the metropolitan region of Belo Horizonte. Its relevance is to know about the ecotoxicity of the effluents, since for this region these data do not exist. In addition, this study allows a better understanding about the characteristics of leachate from this landfills. The database generated can support the planning and the choice of the most effective treatment for this effluent. Monthly collections were made during the period November 2009 to October 2010 and the results showed a high variation for almost all parameters evaluated, and there were a predominance of the difference between the landfill and the landfill finished with the other sites. These differences may indicate important factors as the type of waste and maturation of the leachate. Comparisons were made between young and old landfills, and industrial and sanitary landfill. The results indicate that the organic matter content received by the landfill directs the differences, since the old landfill is no longer receiving waste and industrial landfill does not receive organic matter. he ecotoxicity, through principal component analysis and correlation, was also associated to the alkalinity, total nitrogen, ammoniacal nitrogen, conductivity, total organic carbon, trace metals and cyclic and phenolic compounds. The values of faecal streptococci were significantly higher than the fecal coliforms, suggesting that this variable is a better indicator of fecal contamination for this type of waste, because it shows organisms more resistant to heat, alkaline conditions and high concentrations of salts. The quantified metals are mostly in low and moderate concentrations, and the highest concentrations were showed in the leachate from the landfill A1 and the smallest concentrations in leachate from landfills A3 and A5. Were identified 170 organic compounds, with the largest amount present in the leachate from the landfill A3 and the lower in the leachate from the landfill A5, but the dominance of potentially toxic compounds was in the leachate from the landfill A1. The drugs, present in bigger quantities in the leachate from the landfill A3 seem to have less toxicity than the other compounds